2021
DOI: 10.1259/bjr.20210728
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen (PSMA) fusion imaging in prostate cancer: PET–CT vs PET–MRI

Abstract: Objectives: To investigate whether PET/CT or PET/MRI is more appropriate for imaging prostate cancer, in terms of for primary tumor detection, local staging and recurrence, as well as lymph nodes and distant metastases. Methods: A systematic literature search was conducted on Embase, PubMed/MEDLINE, and the Cochrane Library database. Studies evaluating the diagnostic performance of PET/CT vs PET/MRI in prostate cancer patients were emphasized. Results: We reviewed 57 original research articles during the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, there are no previous studies focusing on the accuracy of combined PSMA PET/CT and mp-MRI imaging in the radiorecurrent setting, with MR-targeted histopathological confirmation available. Previous studies have examined the diagnostic accuracy of PSMA PET/CT or mp-MRI in recurrent prostate cancer, but not in the same setting as in our study, because of differences in primary treatment (all or a subgroup of patients with status after primary prostatectomy or HIFU), location of biopsies (i.e., biopsies of regional or distant metastases), biopsy type (not MR-targeted), or imaging (not a combination of PSMA PET/CT and mp-MRI) [17,36,40,[43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…To the best of our knowledge, there are no previous studies focusing on the accuracy of combined PSMA PET/CT and mp-MRI imaging in the radiorecurrent setting, with MR-targeted histopathological confirmation available. Previous studies have examined the diagnostic accuracy of PSMA PET/CT or mp-MRI in recurrent prostate cancer, but not in the same setting as in our study, because of differences in primary treatment (all or a subgroup of patients with status after primary prostatectomy or HIFU), location of biopsies (i.e., biopsies of regional or distant metastases), biopsy type (not MR-targeted), or imaging (not a combination of PSMA PET/CT and mp-MRI) [17,36,40,[43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 84%
“…In the diagnostic setting before primary treatment of local disease, PPVs between 36 and 100% for PSMA PET/CT [33][34][35][36][37], 34 and 85% for mp-MRI [33][34][35]38], and 67 and 85% [35,39] for combined PSMA PET/CT and mp-MRI are reported. Sensitivity and specificity rates between 64 and 95% and 71 and 95% have been found for PSMA PET/CT and between 67 and 96% and 81 and 100% for PSMA PET/MRI in primary prostate cancer detection [40,41]. For mp-MRI alone, sensitivity rates of 43-96% and specificity rates of 23-98% have been described elsewhere [38,40,41].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Imaging results such as CT/PET-CT and multiparametric MRI/PET-MRI had low sensitivity in identifying lymph node metastases ( 24 , 25 ). Nomograms had been built for predicting lymph node metastases ( 2 , 6 ); these tools also mainly relied on Gleason score and T stage, and we found that the two factors had an impact on the survival benefit of LND, and that extended LND was more likely to remove occult lymph node metastases, as higher Gleason score and T stage were risk factors for lymph node metastasis ( 26 28 ).…”
Section: Discussionmentioning
confidence: 99%